An appraisal of the Philippine Association of Public Secondary School Administrators - Josep, Alfredo Corpin 1926- (s.n.], 1969)
The purpose of the study is to make an appraisal of the Philippine Association of Public Secondary School Administrators (PAPSSA), an educational association working for the advancement of public education, particularly secondary education in the period of 1963-1968. Mass of the information have been supplemented by records of the association, memoranda, circulars, and bulletins of the Bureau of Public Schools.